MOY ALMASHTIRISH SHAHOBCHALARI TIZIMINI AVTOMOTLASHTIRISHNING MA’LUMOTLAR BAZASI - Ortiqov Bekzod Qadamboyevich; Saidnazarova Shohnozabonu Kamolbek qizi; Jumyozov Sarvar Umirbek o‘g‘li; Tursinboyev Ma’rufjon Anvar o‘g‘li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. This article discusses the advantages of creating and using a database of automation of the oil change station system. Based on this database, we have made comments about the possibility of automating oil change stations and improving the quality of car service.